Effect of treating elbow flexor spasticity with botulinum toxin injection and adjunctive casting on hemiparetic gait parameters: A prospective case series - Supun Kotteduwa Jayawarden; Ryan Sandarage; Jordan Farag; Carl Ganzert; Paul Winston; Patricia Mills; Rajiv Reebye (Medical Journals Sweden, 2020)
Objective: To investigate changes in hemiparetic gait parameters after treatment of elbow flexor spasticity with botulinum neurotoxin (BoNT) injection and adjunctive casting. Design: Prospective case series. Subjects: Ten participants with spasticity secondary to acquired brain injury (8 stroke, 2 traumatic brain injury). Interventions: Participants received BoNT injections for their spastic elbow flexors under ultrasound guid-ance. Two weeks post-injection, an elbow stretching cast was applied for 1 week. Outcome measures: Assessments using the Modified Ashworth Scale (MAS), Tardieu scale V1 angle of arrest at slow speed and V3 angle of catch at fast speed, 2-min walk test (2MWT), Edinburgh Gait Score scale (EGS) and video gait analysis for step-length symmetry were conducted pre-BoNT injection (t0) and at cast removal (t1). Goal attainment scale (GAS) was used to assess changes in spasticity and gait 3 months post-injection (t2). Results: At t1, participants showed a mean increase of 16.7° (p < 0.01) on the Tardieu Scale V3 and a mean reduction of 0.5 points on the MAS (p < 0.05). There was also a mean reduction on EGS of 2.7 points (p < 0.05), and a mean increase on 2MWT of 3.1 m (p << 0.05). On the GAS, all participants report-ed impro-ved gait at t2 and 80% reported a decrease in spasticity. Conclusion: Combining BoNT injection with casting for treatment of elbow flexor spasticity without treat-ing the lower limb may improve hemiparetic gait parameters.